The Correlation between Self –Esteem nd English Learning Achievement of the First Year English Education Department Students at Mulawarman University - Novira Anjani; Aridah; A.K Amarullah (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
This study aimed to find out the correlation between students’ self-esteem and English learning achievement of the first-year English Education Department Students at Mulawarman University. The method used in this study was quantitative research which was designed in a correlational study. The total sampling method was used to take the samples, where it was the same with the numbers of population (86 students). The samples were the first-year students of the English Department from three classes. Self-Esteem Questionnaire (QSE) was adopted from Hyde (1979), which was used to find students’ self-esteem. Cumulative scores related to English courses in the first semester were used to find students’ English learning achievement. Descriptive statistics and Pearson Product Moment Correlation were used to analyze the data. The mean score for students’ self-esteem was 75.59, it indicated that the level of self-esteem was vulnerable. While the mean score for students’ English learning achievement was 3.24 which was categorized as Good. The calculation using the Pearson Product Moment showed the r-value was .185 and it was lower than r-table 0.212 with the level of probability (p) significance (sig.2-tailed) was .089 and it was higher than 0.05. It indicated that there was no significant correlation between self-esteem and English learning achievement. The different results were found between English skills subjects and non-English skills subjects with students’ self-esteem. There was a positive slight significant correlation between self-esteem and the subject of English skills, while there was no significant correlation between self-esteem and non-English skills subjects